PENGARUH PENGGUNAAN BRAND AMBASSADOR, KOREAN WAVE, DAN CITRA MEREK TERHADAP MINAT BELI SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN SKINCARE AZARINE - Puspitasari, Dian (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to analyze the effect of Brand Ambassador, Korean Wave, Brand Image on purchase intention and the effect on purchasing decision for Azarine skincare. The research design uses quantitative methods. The data collection tool uses a questionnaire that has been tested for validity and reliability which is distributed via google form. The population analyzed in this study were consumers who buying Azarine skincare products. The number of samples analyzed was 185 consumers. Data analysis was carried out using Smart-PLS (Partial Least Square), with the research instrument being a questionnaire. The variables examined in the study were brand ambassador (X1), Korean wave (X2), brand image (X3), purchase intention (Y1) and purchasing decisions (Y2). The results showed that brand ambassador not affected significantly toward purchase intention, Korean wave affected positive and significantly toward purchase intention, brand image affected positive and significantly toward purchase intention, purchase intention affected positive and significantly toward purchasing decision, brand ambassador affected positive and significantly toward purchasing decision, Korean wave not affected significantly toward purchasing decision, and brand image not affected significantly toward purchasing decision.